EFFICACY AND SAFETY OF ACIDUM ACETYLSALICYLICUM USAGE - V. N. Drozdov; V. A. Kim (Столичная издательская компания, 2016)
Data about efficacy and safety of acetylsalicylic acid usage as antiplatelet drug and for cancer prevention are presented.